Prevalence and Characterization of Chlamydia Psittacie from Birds in Malaysia - Phong , Su Fun (1998)

(untitled)
Chlamydia psittacie causes a range of clinical syndromes, from life threatening systemic disease to an inapparent infection in birds and is a zoonotic disease. The disease is important in many countries with infection rates ranging from 10-40% and carrier rate that could exceed 90%. In Malaysia, no study on avian chlamydiosis has been done. Therefore, this study is conduded to determine the epidemiological and biological properties of Chlamydia psittacie in birds from Malaysia. The surveillance on prevalence rate of Chlamydia psittacie in pigeons, doves and parrots was carried out in the areas of Klang Valley. One hundred and fifty two (152) fresh faecal samples were collected from different species of birds with different management background. The birds were grouped into four categories, namely, pet bird shops, parks, individual pet birds owner and wild birds. The samples were tested with Clearview Chlamydia test kit which was the solid phase sandwich immunoassay using the chromographic principle and direct colour label. Pet bird shops had the significantly highest prevalence rate (81.1%), followed by the category owner (55.9%), park (52.0%) and birds in the wild (25.0%). Among the group of Columbiformes and Psittaciformes, they had no significant difference in their percentage. Birds kept in population had significant higher prevalence rate (78.9%) compared to birds which were kept individually in cages (40.4%). The percentage of birds showing signs of chlamydiosis was 4.6% and the carrier rate was 45.4%. Poor hygiene, sanitation, nutrition, management, crowded confinement, no specific quarantine programme and proper treatment to suspected sick birds led to the highest prevalence rate in pet bird shops. Lack of knowledge in disease control and management were major contributions to high prevalence rate in the categories of individual pet bird owners and recreational parks. Wild doves had lowest prevalence rate probably because they live in less stressful environment. The birds were from different management background and therefore species susceptibility could not be determined. Parakeets and budgerigars had the highest prevalence rates probably because they were most popularly kept as captive birds.